Some Aspects of Petroleum Product Price Adjustment in the Context of Fund Programs, 1980-1982. (IMF Working Papers; Working Paper, 1987)
This paper reviews adjustment in oil imports and domestic pricing policies affecting petroleum under Fund-supported programs. The adjustment of countries with Fund-supported programs (during 1980-82) following the two oil price shocks is compared with that of the nonprogram countries, to evaluate the impact of the Fund's decision to emphasize adjustment after 1979-80 as opposed to providing more financing after 1973-74. The relatively stronger adjustment to the second oil price shock, by program countries underpinned by evidence of adoption of important petroleum pricing policies and support measures in a program context, provides evidence that the Fund contributed to the adjustment and energy conservation effort.